2016
DOI: 10.1016/j.chemosphere.2016.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antibiotic-resistant Escherichia coli isolated from a municipal wastewater treatment plant

Abstract: 41 42The emergence and diffusion of antibiotic-resistant bacteria has been a major public health 43 problem for many years now. In this study, antibiotic-resistance of coliforms and Escherichia 44 coli were investigated after their isolation from samples collected in a municipal wastewater 45 treatment plant in the Milan area (Italy) along different points of the treatment sequence: 46 inflow to biological treatment; outflow from biological treatment following rapid sand 47 filtration; and outflow from peracet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…The mean reduction values of the faecal indicators at specific PAA doses are reported in Figure 1. During the monitoring, high concentrations [2,28] of faecal coliforms and E. coli, as well as enterococci and C. perfringens were observed in raw sewage ( Table 4). The concentrations of the four bacterial indicators were similar in the summer, autumn, and spring (range: 2.91 to 4.42 log MPN/100 mL or CFU/100 mL), whereas a major contamination was observed during the winter (range: 4.21 to 5.74 log CFU-MPN/100 mL or CFU/100 mL).…”
Section: Salmonella E Coli O157:h7 Campylobactermentioning
confidence: 99%
See 1 more Smart Citation
“…The mean reduction values of the faecal indicators at specific PAA doses are reported in Figure 1. During the monitoring, high concentrations [2,28] of faecal coliforms and E. coli, as well as enterococci and C. perfringens were observed in raw sewage ( Table 4). The concentrations of the four bacterial indicators were similar in the summer, autumn, and spring (range: 2.91 to 4.42 log MPN/100 mL or CFU/100 mL), whereas a major contamination was observed during the winter (range: 4.21 to 5.74 log CFU-MPN/100 mL or CFU/100 mL).…”
Section: Salmonella E Coli O157:h7 Campylobactermentioning
confidence: 99%
“…Zanotto et al [28] detected ampicillin-and chloramphenicol-resistant E. coli in the influent and effluent from a municipal WWTP in the Milan area (Italy). The WWTP applied a final disinfection with PAA (approximately 2.0 mg/L, 45 min contact time).…”
Section: Salmonella E Coli O157:h7 Campylobactermentioning
confidence: 99%
“…Moreover, dissemination of ARGs may also be affected by wastewater contamination with heavy metals, whose residues may pose co-selection pressure on ARG distribution [24]. For this reason, ARGs are not effectively eliminated in the wastewater treatment process and their concentration may even increase [39]. Wastewater discharge to the environment or their re-utilisation may lead to the dissemination of ARB and ARGs in the environment, threatening the ecological safety of aquatic ecosystems, in particular [27,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, rapid decrease of ARB was observed after the disinfection with only 8 μg/ml ampicillin. About 78% of the resistant E. Coli were reported resistant to 32 μg/ml ampicillin [17]. Studies of a certain WWTP in Jedah, Saudi Arabia have also been reported.…”
Section: Arb Occurrence In Wwtpmentioning
confidence: 99%